1986
DOI: 10.1111/j.2042-3306.1986.tb03636.x
|View full text |Cite
|
Sign up to set email alerts
|

Faecal composition in foal heat diarrhoea

Abstract: Summary Developmental changes of the gastrointestinal tract were probably responsible for the changes in faecal composition during the first week of the foals' life, which resembled small intestinal ingesta of adult horses, suggesting a minimal colonic modification. Faecal composition at the time of foal heat diarrhoea was suggestive of a secretory‐type diarrhoea, in that the electrolyte concentration accounted for most of faecal osmolality and the faecal pH was alkaline. After foal heat diarrhoea faecal compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…composition during foal heat diarrhea is suggestive of a secretory-type diarrhea, with higher electrolyte concentrations than is normal [3]. In addition, the fecal pH level was found to be alkaline, and fecal osmolality and volatile fatty acid concentrations decreased with the onset of diarrhea.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…composition during foal heat diarrhea is suggestive of a secretory-type diarrhea, with higher electrolyte concentrations than is normal [3]. In addition, the fecal pH level was found to be alkaline, and fecal osmolality and volatile fatty acid concentrations decreased with the onset of diarrhea.…”
mentioning
confidence: 88%
“…In addition, the fecal pH level was found to be alkaline, and fecal osmolality and volatile fatty acid concentrations decreased with the onset of diarrhea. The authors concluded that their data suggests a hypersecretion in the small intestinal mucosa, which was not compensated for by the immature colon [3]. These findings, along with a temporal association with coprophagy, suggest that the diarrhea occurs in response to the establishment of normal GI flora.…”
mentioning
confidence: 96%
“…Noninfectious causes include foal heat diarrhea, perinatal asphyxia syndrome, necrotizing enterocolitis (NEC), dietary imbalance, equine gastric ulcer syndrome, luminal irritant diarrhea, and secondary lactose intolerance. 16,17 The most common infectious agents include rotavirus (RV), Clostridium perfringens types A and C, Salmonella spp, C difficile, Cryptosporidia, and L intracellularis. 2,3,6,11,15,17 Less common causes are Coronavirus, Rhodococcus equi, and Strongyloides westeri.…”
Section: Etiologymentioning
confidence: 99%
“…It occurs in 75% to 80% of neonatal foals and usually lasts 3 days to 4 days. 16 These foals have diarrhea, show no signs of systemic disease, and continue to suckle well. 2 Individual foals may be affected by more severe and prolonged diarrheic episodes.…”
Section: Foal Heat Diarrheamentioning
confidence: 99%
“…Although the exact cause has not been established, the diarrhoea is currently thought to be hypersecretory in origin and most likely associated with the establishment of a normal gastrointestinal flora (Masri et al 1986). Foals remain bright, alert and systemically healthy and specific treatment is not necessary.…”
Section: Foal Heat Diarrhoeamentioning
confidence: 99%